An essential role for interleukin 10 in the function of regulatory T cells that inhibit intestinal inflammation - Asseman, C; Mauze, S; Mauze, S; Leach, M; Leach, M; Coffman, R; Coffman, R; Powrie, F; Powrie, F (Rockefeller University Press, 1999)
A T helper cell type 1-mediated colitis develops in severe combined immunodeficient mice after transfer of CD45RB(high) CD4+ T cells and can be prevented by cotransfer of the CD45RB(low) subset. The immune-suppressive activities of the CD45RB(low) T cell population can be reversed in vivo by administration of an anti-transforming growth factor β antibody. Here we show that interleukin (IL)-10 is an essential mediator of the regulatory functions of the CD45RB(low) population. This population isolated from IL-10- deficient (IL-10(-/-)) mice was unable to protect from colitis and when transferred alone to immune-deficient recipients induced colitis. Treatment with an anti-murine IL-10 receptor monoclonal antibody abrogated inhibition of colitis mediated by wild-type (WT) CD45RB(low) CD4+ cells, suggesting that IL-10 was necessary for the effector function of the regulatory T cell population. Inhibition of colitis by WT regulatory T cells was not dependent on IL-10 production by progeny of the CD45RB(high) CD4+ cells, as CD45RB(low) CD4+ cells from WT mice were able to inhibit colitis induced by IL-10(-/-) CD45RB(high) CD4+ cells. These findings provide the first clear evidence that IL-10 plays a nonredundant role in the functioning of regulatory T cells that control inflammatory responses towards intestinal antigens.